Lead jurisdiction concepts: Towards rationalizing multiple competition policy enforcement procedures - Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2014)
Lead jurisdiction models represent one option how to extend and enhance contemporary interagency cooperation among competition policy regimes. They constitute a multilateral, case-related form of cooperation that is suited to effectively create a one-stop-shop for the prosecution of international cartels, the handling of cross-border mergers and acquisitions and the governance of international antitrust cases. Thus, lead jurisdiction models offer considerable economic benefits. However, they also entail several caveats. Three possible working problems and downside effects of lead jurisdiction models in international competition policy enforcement are discussed in this paper.
Keywords: F02; F53; F55; K21; L40; D02; 330; international competition policy; lead jurisdiction models; international governance; interjurisdictional cooperation; interagency cooperation; competition economics; antitrust